Hypertensive response to exercise: mechanisms and clinical implication - Kim, Darae (Clin Hypertens, 2016)
A hypertensive response to exercise (HRE) is frequently observed in individuals without hypertension or other cardiovascular disease. However, mechanisms and clinical implication of HRE is not fully elucidated. Endothelial dysfunction and increased stiffness of large artery contribute to development of HRE. From neurohormonal aspects, excess stimulation of sympathetic nervous system and augmented rise of angiotensin II seems to be important mechanism in HRE. Increasing evidences indicates that a HRE is associated with functional and structural abnormalities of left ventricle, especially when accompanied by increased central blood pressure. A HRE harbors prognostic significance in future development of hypertension and increased cardiovascular events, particularly if a HRE is documented in moderate intensity of exercise. As supported by previous studies, a HRE is not a benign phenomenon, however, currently, whether to treat a HRE is controversial with uncertain treatment strategy. Considering underlying mechanisms, angiotensin receptor blockers and beta blockers can be suggested in individuals with HRE, however, evidences for efficacy and outcomes of treatment of HRE in individuals without hypertension is scarce and therefore warrants further studies.